2019
DOI: 10.1111/luts.12293
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results in women with detrusor underactivity and stress urinary incontinence undergoing suburethral sling procedure—Predictive factors for successful outcome

Abstract: Objectives: To elucidate the treatment results and predictors for successful outcome in women with detrusor underactivity (DU) and stress urinary incontinence (SUI) undergoing suburethral sling procedure.Methods: Medical records of women with coexistent SUI and DU treated with a suburethral sling were retrospectively reviewed and we analyzed the association between treatment outcome and baseline demographics including etiology of DU and urodynamic variables. Patients who were dry and could urinate spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…CIC for voiding dysfunction after anti-incontinence surgery is conducted 3 to 4 times daily until the PVR decreases to less than 100 mL or is at most half of the voided volume [33]. Although the results may vary depending on the preoperative patient characteristics, more than 20% of the patients required CIC after a MUS in a study of SUI patients with DU who had more than 180 mL mean preoperative PVR [16]. Incontinence patients with UAB who can only empty their bladder through CIC are more likely to maintain CIC after incontinence treatment.…”
Section: Clean Intermittent Catheterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…CIC for voiding dysfunction after anti-incontinence surgery is conducted 3 to 4 times daily until the PVR decreases to less than 100 mL or is at most half of the voided volume [33]. Although the results may vary depending on the preoperative patient characteristics, more than 20% of the patients required CIC after a MUS in a study of SUI patients with DU who had more than 180 mL mean preoperative PVR [16]. Incontinence patients with UAB who can only empty their bladder through CIC are more likely to maintain CIC after incontinence treatment.…”
Section: Clean Intermittent Catheterizationmentioning
confidence: 99%
“…The 10-year continence rate in DU was 79.4%, which was not different from the outcomes of the patients with stable bladder or DO. Another study elucidating the outcome of retropubic MUS in SUI with DU showed that 76% of the patients had clinical improvement in their SUI, but 21% of the patients needed clean intermittent catheterization (CIC) to empty their bladder [ 16 ]. DU was defined by a PdetQmax of <20 cm H 2 O and a Qmax of <15 mL/sec in that study.…”
Section: Managementmentioning
confidence: 99%
“…Different studies showed that DUA could be related to a prolonged return to normal voiding and higher post-operative urinary complications [ 19 , 25 ]. Others found that preoperative Pdet/Qmax [ 18 ] or Qmax [ 20 ] could be predictive factors of a negative effect of DUA on SUI surgical outcomes. However, the lack of correlation between DUA and the type of SUI did not allow an assessment of whether DUA or C-SUI affected the voiding complications.…”
Section: Discussionmentioning
confidence: 99%
“…C-SUI and DUA are recognized as potential conditions affecting MUS results; however, available studies have assessed these factors only separately, not analysing the relationship between C-SUI and DUA and the potential impact of DUA on the results of the type of SUI [ 18 , 19 , 20 ]. Our research aimed to clarify the influence of each of these conditions – the type of SUI and detrusor impairment – on MUS positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Without a preoperative UDS or video UDS to identify DO, anti-incontinence treatment might fail to completely eradicate incontinence [5] . In addition, BOO and DU can also coexist in women with ISD and women might urinate efficiently because of low urethral resistance [4] , [6] . These LUTDs might become prominent after anti-incontinence surgery, and patients might need revision after surgery.…”
mentioning
confidence: 99%